Simulasi Dinamik Pada Slider Pembawa Crankshaft Otomatis - Wipiansyah Valendrata , Satrio; Karyadi; Aulia Nanda, Rizki; Amir (Jurnal Teknik Mesin Sinergi, 2026)
This study investigates a slider system used to transfer a CNC-manufactured crankshaft to the next production stage through dynamic simulation prior to motor installation. The simulation aims to determine the velocity, acceleration, and displacement of the slider under the influence of the crankshaft mass and applied torque in order to select a suitable driving motor. The research begins with the design and fabrication of the slider, followed by the definition of design parameters, including torque variations of 100, 130, and 150 N·mm, a travel length of 1 m, a crankshaft mass of 7.8 kg, and gravitational acceleration of 9.81 m/s². The dynamic simulation is performed by applying rotational input to the wheel, defining contact interactions between the wheel and the rail, and assembling the wheel with the rail track. The results show that among the three torque variations, the highest velocity and acceleration occur at a torque of 100 N·mm, yielding a velocity of 174.9 mm/s, an acceleration of 22 mm/s², and a reaction force of 1.47 × 10³ N, resulting in a travel time of 11 s to cover a 1-meter track.